2008
DOI: 10.1016/j.ejcts.2007.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after entry closure and aneurysmal wall plication for type B aortic dissection☆

Abstract: Objective: To examine the long-term outcomes after entry closure and aneurysmal wall plication for type B chronic dissecting aortic aneurysm. This procedure uses no artificial graft and preserves all intercostal arteries. Methods: We reviewed the records of 40 consecutive patients who underwent this procedure between September 1983 and December 2002. The mean age at operation was 60 AE 12 years (range, 38-79 years). The mean follow-up period was 9.8 AE 5.1 years (range, 4-23 years). Follow-up was completed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Another study indicated that TEVAR was only a 'complication-specific' indication (28). The remaining six studies from the endovascular era did not provide any evidence that they also perform endovascular repairs (29)(30)(31)(32)34,36), while another did not state indication for OSR (2).…”
Section: Demographic and Operative Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…Another study indicated that TEVAR was only a 'complication-specific' indication (28). The remaining six studies from the endovascular era did not provide any evidence that they also perform endovascular repairs (29)(30)(31)(32)34,36), while another did not state indication for OSR (2).…”
Section: Demographic and Operative Techniquesmentioning
confidence: 99%
“…Nine studies did not specify indications for surgery (2,16,17,24,25,29,32,33,36). In series from institutions that also reportedly performed TEVAR, indications for open repair included extensive involvement of the aorta (33,35) or connective tissue disease (35).…”
Section: Demographic and Operative Techniquesmentioning
confidence: 99%
See 3 more Smart Citations